2019
DOI: 10.1542/peds.2018-2185
|View full text |Cite
|
Sign up to set email alerts
|

Two Family Interventions to Reduce BMI in Low-Income Urban Youth: A Randomized Trial

Abstract: BACKGROUND: Our primary aim was to evaluate the effects of 2 family-based obesity management interventions compared with a control group on BMI in low-income adolescents with overweight or obesity. METHODS:In this randomized clinical trial, 360 urban-residing youth and a parent were randomly assigned to 1 of 2 behaviorally distinct family interventions or an education-only control group. Eligible children were entering the sixth grade with a BMI $85th percentile. Interventions were 3 years in length; data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…Of the remaining 42 trials that reported no statistically significant between‐group change in dietary intake, exploratory analysis identified 28 RCTs where there was significant change in intake within one intervention arm (see Supporting information, Table S2). Fourteen studies reported no statistically significant change in any dietary outcome variables ( 13‐26 ) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the remaining 42 trials that reported no statistically significant between‐group change in dietary intake, exploratory analysis identified 28 RCTs where there was significant change in intake within one intervention arm (see Supporting information, Table S2). Fourteen studies reported no statistically significant change in any dietary outcome variables ( 13‐26 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐three percent of studies ( n = 47) did not specifically mention diet adherence, 27% ( n = 29) described diet adherence methods in the methodology, and 21% ( n = 21) reported adherence based on programme attendance or log‐ins. Dietary intake assessment was primarily conducted using repeat 24‐h recalls ( n = 25) ( 16,20,22,30,35,39,40,46,56,58,60,65,70,74,83,88,89,92,99‐101,104,105,112,114 ) or ≥3‐day WFRs or food diaries ( n = 25) ( 48,51,53,54,57,61,62,67‐69,73,74,78,84‐86,91,95,97,98,107‐109,111,113 ) . Eighteen studies used multiple dietary assessment methods ( 19,29,39,44,45,57,58,60,62,74,82,86,92,95,101,103,112,116 ) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other intervention arm, not reviewed here, was the SystemsCHANGE intervention which focused on restructuring family environment and a series of family-designed small experiments. Neither of the family-based interventions improved BMI slope (primary outcome) over 3 years or health-related secondary outcomes (Moore et al, 2019).…”
Section: Minnesota's Net-work Interventionmentioning
confidence: 96%